The Effect of Acids, Bases and Salts in Removing Rust Using the Electrolysis Method - Kurniawan, Ekin Dwi Arif; Moondra Zubir; Alfira Julian Pratiwi; Rafidah Almira Samosir; Mutia Ardila; Agnes Aprilyani Br Silitonga; Anna Sakila; Dindy Louiza Pangaribuan; Geby Mai Irawan; Okta Miranda Samosir; Vivy Cintia Laudia Hutagaol (Universitas Negeri Medan, 2025)
Corrosion is a natural process of metal deterioration caused by chemical or electrochemical reactions with the surrounding environment, and it commonly occurs in iron and steel. This study examined the use of electrolysis as a simple method to reduce rust on iron surfaces by applying several electrolyte solutions. The solutions tested included sodium chloride, citric acid, acetic acid, sodium bicarbonate, and water, each at a concentration of 10%, while citric acid was also varied up to 100%. Electrolysis was performed for 10 to 30 minutes on both positive and negative poles. The findings showed that sodium chloride solution gave the highest effectiveness in rust removal, with 0.93% rust loss on the negative pole and 0.58% on the positive pole. Increasing solution concentration and treatment time further improved the rust removal rate, reaching 2.50% at 30 minutes.